Comparative analyses of cytohistologic techniques in diagnoses of lung lesions - Tuladhar, A; Panth, R; Joshi, AR (Journal of Pathology of Nepal, 2011)
Background: The use of cytological methods in the diagnosis of malignant lesions of the respiratory tract has been generally acclaimed as one of its most successful applications. Flexible fiberoptic bronchoscopy revolutionized respiratory cytology, as bronchial brushings, broncho-alveolar lavage and bronchial forceps biopsy became more easy, accessible and popular, shifting the emphasis from diagnosis of advanced malignancy in inoperable patients to the use of cytology as a first line diagnostic and management tool. Respiratory tract cytology is well established throughout the world as a diagnostic procedure in the evaluation of patient with suspected lung malignancy. Materials and Methods: A prospective study was conducted on 50 patients divided in two groups who underwent fiberoptic bronchoscopy during the period from November 2007 to October 2008 at the Department of Cardiovascular and Thoracic Unit, Bir Hospital. Group I consisted of 35 cases of suspected lung malignancy on clinical and radiological examination, while group II consisted of 15 cases of non-neoplastic lung diseases. Results: Bronchial brushing and forceps biopsy showed a sensitivity of 50% and 84.21% respectively in the diagnosis of malignancy. Broncho-alveolar lavage revealed malignancy in 66.7% patients. Transthoracic needle aspiration had the highest sensitivity of 100% whereas bronchial wash was revealed malignancy only in 17.4% of the cases. Conclusion: Combination of various cytohistological techniques complements each other and enhances the diagnostic efficacy of various neoplastic and non-neoplastic lung diseases. Bronchial brushing, forceps biopsy and transthoracic needle aspiration are complimentary in diagnosis of various lung malignancies whereas broncho-alveolar lavage is a useful procedure in detection of infections diseases. Keywords: Fiberoptic bronchoscopy; Lund cancer; Infection; Cytohistologic technique DOI: http://dx.doi.org/10.3126/jpn.v1i2.5407 JPN 2011; 1(2): 126-130